The Effect of Think Pair Share Learning Method Using Observation Approach Toward the Cognitive Learning Outcome of Senior High School Student Preferences the Study of Biology Lesson - Nurul Aslami; Suratno Suratno; Erlia Narulita (Pancaran Pendidikan, 2021)
The current learning process of students is directed in a one way process. The teachers have to explain and the students are listening to them instead of being actively involved. It degrades their cognitive learning outcome. The application of Think Pair Share affects the students to become actively involved and giving an opportunity for those who want to comprehend their argument into the class. The additional approach of the method may support to make the students feel their own learning method which goes meaningful. The goal of this research is to know the role of Think Pair Share learning method toward the cognitive learning outcome of senior high school students. The research uses quassi experiments in terms of control class and experiment class approach. The result shows that the reduction of them are 33,53 and 17,21. The normality test result defines that the significance value is 0,0066 (>0,05). It means they have accepted H0, meanwhile the pretest and posttest mark of each class control and experiment distribute normally. The homogeneity test results show a value of 0.439 (> 0.05) so that H0 is accepted, which means that the pretest and posttest values from the experimental and control classes come from the same or homogeneous population. The result of ANACOVA test show that SPSS result is 0,000 (>0.05) so the H1 is accepted. It proves that Think Pair Share method using observation experiment is effectively significant towards the cognitive learning outcome of the students. From this situation, it concludes that the approach is having an impact into the cognitive learning outcome of the students